Pengaruh Media Video Edukasi terhadap Tingkat Pengetahuan Ibu tentang Penanganan Kejang Demam - Pratiwi, Ratih Nadhira; Susmarini, Dian; Purnamasari, Meivita Dewi; Purwandari, Haryatiningsih; Fitriyani, Aris (Prodi Keperawatan Purwokerto, 2024)
Background: Handling febrile seizures in toddlers that we often encounter such as putting a spoon into the mouth can cause airway obstruction and lead to difficulty breathing. This can harm the child and make the febrile seizures worse. The efforts were made to improve the mother’s knowledge about handling febrile seizures by using animated educational videos. The attractive animated video helps to understand the materials and increases the mother’s knowledge. Handling febrile seizures in toddlers that we often encounter such as putting a spoon into the mouth can cause airway obstruction and lead to difficulty breathing. This can harm the child and make the febrile seizures worse. The efforts were made to improve the mother’s knowledge about handling febrile seizures by using animated educational videos. The attractive animated video helps to understand the materials and increase the mother’s knowledge. Objective: The purpose of giving education was to analyze the effect of educational videos on the level of mother’s knowledge in handling febrile seizures. Methods: The type of study was a quasi-experimental pretest-posttest control group design. The samples were collected by simple random sampling and both groups were 44 respondents. The instrument is a Knowledge Questionnaire. about the characteristics of respondents and their knowledge about febrile seizures. Data analysis used paired sample t-test dan independent t-test. Results: The result showed that education with video significantly improves the knowledge of mothers on handling febrile seizures (p=0.000). Conclusion: The education video presented to the respondents improved the level of mother’s knowledge in handling febrile seizures